UNILATERAL CLAIM OVER CHAGOS ARCHIPELAGO AS BRITISH INDIAN OCEAN TERRITORY (BIOT) BY UNITED KINGDOM BASED ON INTERNATIONAL LAW - Jerina Novita Elpasari (International Law Department, Faculty of Law Universitas Padjadjaran, 2019)
AbstractIn 1965, United Kingdom (UK) made a unilateral claim over the Chagos Archipelago as British Indian Ocean Territory (BIOT) based on the BIOT Order of 1965 and Statutory Instrument of 1965 No. 1020. Due to this unilateral act, the Chagos Archipelago no longer parts of Mauritius. Problem arising from Britain's unilateral claim to the territory was further aggravated by the United Kingdom’s act in enforcing population transfer towards all Chagos islanders (Chagossians) out of the territory without adequate compensations and resettlement. This research aims to analyze the legality of unilateral claims over the Chagos archipelago as a BIOT and the enforced transfer of Chagossians from their original residential place by the United Kingdom. It argues that under international law, Chagos Archipelago is recognized as an area that should remain integrated within the territory of Mauritius. It further argues that the UK has violated international law by committing enforced population transfer.Keywords: BIOT, Enforced Population Transfer, Territory, The Chagos Archipelago, Unilateral Act. AbstrakPada tahun 1965, Inggris melakukan klaim sepihak atas wilayah Kepulauan Chagos sebagai British Indian Ocean Territory (BIOT) berdasarkan British Indian Ocean Territory Order of 1965 dan Statutory Instrument of 1965 No. 1020. Kepulauan Chagos merupakan bagian dari Mauritius pada saat Mauritius berada dibawah penjajahan Inggris. Tindakan yang dilakukan oleh Inggris terhadap wilayah tersebut berdampak pada terpisahnya kepulauan Chagos dari Mauritius. Permasalahan yang timbul dari Klaim sepihak Inggris atas wilayah tersebut kemudian turut diperparah dengan tindakan Inggris yang melakukan pemindahan paksa seluruh penduduk kepulauan Chagos (Chagossians) dari wilayah tersebut tanpa kompensasi dan tempat tinggal pengganti yang layak serta memadai. Penelitian ini bertujuan untuk menganalisis legalitas klaim sepihak terhadap kepulauan Chagos sebagai BIOT dan pemindahan Chagossians dari tempat tinggal asalnya secara paksa yang dilakukan oleh Inggris sebagai enforced population transfer. Penelitian ini menunjukkan bahwa wilayah kepulauan Chagos diakui sebagai wilayah yang seharusnya tetap terintegrasi dalam wilayah Mauritius dan penetapan wilayah tersebut sebagai BIOT telah bertentangan dengan prinsip dan ketentuan hukum internasional. Kata Kunci: BIOT, Enforced Population Transfer, Kepulauan Chagos, Tindakan Sepihak, Wilayah